Experiences of Indonesian women with breast cancer underwent treatment decision-making: A qualitative study - Sitanggang, Yenni Ferawati; Lin, Hung-Ru (Belitung Raya Foundation, Indonesia, 2024)
Background: Patients with breast cancer face a complex situation upon receiving their diagnosis and considering future treatment options. In Indonesian culture, relatives and others significantly influence decision-making processes. Understanding the perspectives of Indonesian women with breast cancer regarding treatment decision-making can enhance satisfaction with the care provided. Objective: This study aimed to explore the experiences of Indonesian women with breast cancer regarding treatment decision-making. Methods: A qualitative descriptive study design was utilized. Purposive sampling was employed to select the study participants. In-depth interviews were conducted with 15 women with breast cancer between March and June 2023. The data were analyzed using thematic analysis. Results: Three main themes were developed: 1) Emotional impact and uncertainty in cancer care, 2) Clear communication and support for patients, and 3) Family-centered decision-making in treatment planning. Conclusion: This study highlights the perspectives of Indonesian women with breast cancer on treatment decision-making. Nurses play a crucial role in providing clear information to patients and their families during the decision-making process. Understanding the experiences of women with breast cancer can help support and empower patients through effective communication while they undergo treatment.